STRATEGI MSDM INTERNASIONAL DALAM MENGELOLA TENAGA KERJA GLOBAL PADA INDUSTRI MULTIKULTURAL [INTERNATIONAL HRM STRATEGY IN MANAGING GLOBAL WORKFORCE IN MULTICULTURAL INDUSTRIES] - Budyawan Herijanto; Nurhaeni Sikki; Ai Wiwin Indrawati; Muhammad Arsyad Purba; Nova Karlina; Mochammad Ghalib Fikhrin (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Globalization presents new challenges in human resource management in multinational companies operating in multicultural environments. This Research aims to identify and analyze effective international Human Resource Management (HRM) strategies in dealing with the cultural diversity of the global workforce. The method used is qualitative with a descriptive-analytical case study approach, which focuses on library research. Secondary data was collected through a systematic review of scientific journals, academic books, and other relevant documents, then analyzed using thematic analysis techniques to find appropriatę HRM strategy patterns. The results show that a strategy. that combines cultural adaptation and cross country coordination can improve the effectiveness of global workforce management. The implications of this research show the importance of implementing HRM that is flexible, Inclusive, and adaptive in facing global challenges and maximizing the potential of cultural diversity in multinational organizations.